2015
DOI: 10.1371/journal.pone.0120326
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Transcriptionally Responsive to the Loss of MLL Fusions in MLL-Rearranged Acute Lymphoblastic Leukemia

Abstract: Introduction MLL-rearranged acute lymphoblastic leukemia (ALL) in infants (<1 year) is characterized by high relapse rates and a dismal prognosis. To facilitate the discovery of novel therapeutic targets, we here searched for genes directly influenced by the repression of various MLL fusions.MethodsFor this, we performed gene expression profiling after siRNA-mediated repression of MLL-AF4, MLL-ENL, and AF4-MLL in MLL-rearranged ALL cell line models. The obtained results were compared with various already estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We also tested palbociclib on a t(8;21) AML sample from a relapse patient and observed high drug sensitivity with a 5-fold reduced cell number upon treatment with 300 nM palbociclib ( Figure 7 C). Primary t(8;21)-negative AML cells showed an overall trend of being less sensitive to palbociclib compared with t(8;21)-positive AML ( Figures 7 A and S7 D), although there was some heterogeneity in response concomitant with reported sensitivity in other AML subtypes ( Placke et al., 2014 , Uras et al., 2016 , van der Linden et al., 2015 ). Notably, palbociclib sensitivity did not strictly correlate with cell expansion, possibly due to proliferation masked by cell-death-associated loss of cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested palbociclib on a t(8;21) AML sample from a relapse patient and observed high drug sensitivity with a 5-fold reduced cell number upon treatment with 300 nM palbociclib ( Figure 7 C). Primary t(8;21)-negative AML cells showed an overall trend of being less sensitive to palbociclib compared with t(8;21)-positive AML ( Figures 7 A and S7 D), although there was some heterogeneity in response concomitant with reported sensitivity in other AML subtypes ( Placke et al., 2014 , Uras et al., 2016 , van der Linden et al., 2015 ). Notably, palbociclib sensitivity did not strictly correlate with cell expansion, possibly due to proliferation masked by cell-death-associated loss of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Since CCND2 binds to CDK4 and CDK6 ( Matsushime et al., 1992 , Meyerson and Harlow, 1994 , Xiong et al., 1992 ), we explored whether RUNX1/ETO-expressing cells were sensitive to the CDK4/6 inhibitor palbociclib (PD-0332991) similar to MLL-rearranged (MLLr) and FLT3-ITD-positive leukemia ( Placke et al., 2014 , Uras et al., 2016 , van der Linden et al., 2015 ). t(8;21) AML cell proliferation and clonogenic potential were highly sensitive to palbociclib with GI 50 values (concentration of drug to cause 50% reduction in proliferation of cancer cells) below 50 nM and did not resume proliferation during 18 days of drug exposure ( Figures 6 A–6C).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies [ 10 , 11 , 14 , 15 ] reported that MLL-r positive compared to MLL-r negative children had a higher proportion of patients with poor early treatment response in addition to more risk factors at initial diagnosis. In the current study, we also found that the proportion of M1 patients on Day 15 of induction chemotherapy in MLL-r positive children with ALL was significantly lower than that in the negative group, and the proportion of MRD positive patients on Day 33 was significantly higher than that in the negative group, suggesting that the poor early treatment response in MLL-r positive patients may be due to the dominant clone of MLL-r positive leukemia cells being insensitive or resistant to chemotherapy at the time of initial diagnosis, rather than chemotherapy “selected” for the inferior clone [ 16 , 17 ]. However, after one course of standardized induction chemotherapy, the percentage of MLL-r positive patients with CR of BM could reach 96.8%, which is similar to the 97.6% CR rate reported in China [ 10 ], which might be related to the early strong chemotherapy.…”
Section: Discussionmentioning
confidence: 99%